PERSEPSI MAHASISWA PENJASKESREK PADA MATA KULIAH PENDIDIKAN JASMANI OLAHRAGA ADAPTIF UNIVERSITAS ISLAM RIAU - Merlina Sari; Novia Nazirun; Zulhendri Zulhendri (Journal of Education and Teaching, 2020)
In this case the writer wants to reveal a small part of the perception of Penjaskesrek students in the Adaptive Physical Education course of the Islamic University of Riau. This research is a descriptive research. The population in this study were all Penjaskesrek students taking Adaptive Physical Education courses. While the sample in this study was 128 students from 320 people with purposive sampling technique. The results of this study that the factors opening up the lesson by 87.27%, 81 students attend attendance, 95%, 78 students motivation, 71%, memory of students with past material 57.61%, readiness of students to accept new material 70.81%, core activities 77.22%, and the cover 66.74%. After conducting research directly in the field, a satisfying result is seen where students have a good perception of the learning process of Adaptive Sports Physical Education itself. Then it can be concluded that the students' perception of the Adaptive Physical Education Process is in the good category.